The Rashba effect in two-dimensional hybrid perovskites: the impacts of halogens and surface ligands. Issue 45 (10th November 2022) - Liu, Beichen; Gao, Huaxiong; Meng, Chaoying; Ye, Honggang
Abstract : The distortion of octahedrons will introduce Rashba effect in 2D hybrid organic–inorganic perovskites. Abstract : Two-dimensional (2D) hybrid organic–inorganic perovskites (HOIPs) have gained much research interest nowadays due to their outstanding optoelectronic properties; however, the properties of the Rashba effect in 2D HOIPs have not been fully interpreted. In this work, a detailed thickness dependent structural distortion along with the Rashba splitting energy were investigated. Three types of HOIPs, 2D MAPbCl3, 2D MAPbBr3 and 2D MAPbI3, were adopted to compare the effect of halogens; and three surface ligands, BA, tert -BA and PEA, were adopted to explore the effect of ligands. It turns out that the structural distortion degree decreases with oscillations as the thickness increases, the Rashba splitting magnitude follows the same tendency, and 2D MAPbI3 is less sensitive to the thickness change compared to 2D MAPbBr3 or 2D MAPbCl3 . Furthermore, different ligands and their orientations could have dramatically different impacts on the Rashba splitting. The PEA ligands enhance the Rashba splitting magnitude while the BA ligands have the reverse effect, and the impact of tert -BA ligands is insensitive to the increasing thickness. The partial charge density analysis shows that the band edges could be contributed by a charge density at a specific layer in the structure; thus, the Rashba effect is layer dependent in 2D HOIPs. These results provide some new perspectives on the Rashba effect in 2D HOIPs.